Determination of Cu2+ and biothiols by novel red fluorescent hybrid nanoparticles. Issue 22 (22nd May 2018) - Zhang, Ling; Wang, Zizhun; Hou, Jiaze; Lei, Lulu; Li, Jiao; Bai, Juan; Huang, Hui; Li, Yongxin
Abstract : Red fluorescent hybrid nanoparticles (NPG@PFBD) have been designed and synthesized successfully. Abstract : Red fluorescent hybrid nanoparticles (NPG@PFBD) have been designed and synthesized successfully. The NPG@PFBD nanoparticles are composed of a fluorescent semiconducting polymer (PFBD) and n -propyl gallate (NPG). Because of the coordination between the gallate and Cu 2+, Cu 2+ could attach to the hybrid nanoparticles and quench their fluorescence through photoinduced electron transfer (PET). In addition, in the presence of biothiols, such as glutathione (GSH), Cu 2+ would bind to the thiol. The PET between the hybrid nanoparticles and Cu 2+ was weakened, and the fluorescence signal of the nanoparticles was recovered. A facile detection method for Cu 2+ and biothiols was therefore developed. The detection limit for Cu 2+ and GSH was 40 nM and 90 nM, respectively. The proposed fluorescent hybrid nanoparticles have great potential application for Cu 2+ and GSH detection in related biological fields.